Achievements, Contributions and Scientific Legacy of the Professors in the Accounting and Analysis Department of UNWE Dealing with Economic Activity Analysis (UNWE Yearbook, 2023)
Since the very beginning of the establishment of the Free University of Political and Economic Studies in 1920, the academic disciplines Accounting, Business Calculus and Balance Sheet Studies have been taught in Sofia.During the academic year 1950 – 1951, the discipline Analysis of Economic Activity is introduced in the curriculum for the Business Accounting specialty.The objective of this study is to present the opinions and views of the professors in the Accounting and Analysis Department of the University of National and World Economy (UNWE) who have worked and dealt in the field of economic activity analysis in the course of years. The scientific theory of the economic activity analysis, which is now called financial and business analysis, has its own scientific metrics, such as subject and object; method, techniques and methodology; scope and content; objectives and tasks; functions and principles, which are typical of it and distinguish it from other scientific areas. The scientific theory of the economic activity analysis has been developed, enhanced, deepened and ascertained in the course of the historic development of the scientific thinking in the Accounting and Analysis Department of UNWE since the establishment of the University in 1920 until nowadays – the year 2022.Based on the historic approach, the study presents the views, achievements and contributions of the academic authors, professors and teachers who have worked in the Accounting and Analysis Department of UNWE during a 102-year-period since the establishment of the department and the university. The publication outlines the contributions of scholars who laid the scientific foundations of the theory of the economic activity analysis. The specific theoretic works and decisions of the academic authors in the department on key methodological issues within the contents of the economic activity analysis find their actual application and enrich the economic practice in the country during the various historic stages and public and economic contexts in the course of its development. It has established and still establishes the leading positions of UNWE in students’ education and successful realization in the field of economics and finance.